A method for manufacturing a grinding-free composite insulator core rod

Through the grinding-free composite insulator mandrel manufacturing method, specific rubber formulas and process steps are adopted to solve the problem of reduction in accuracy and dust pollution caused by grinding after mandrel forming, and the strength of the interface connection between the mandrel and the metal is improved and the composite insulator is achieved. Improves stability.

CN118430910BActive Publication Date: 2025-02-07GUANGZHOU MPC POWER INT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410575660.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-02-07
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

The existing composite insulator core rods need to be polished after forming, resulting in a reduction in shape and dimensional accuracy, affecting the reliability and consistency of the crimping of the insulator metal. At the same time, dust pollutes the environment and harms health during the grinding process.

Method used

Using the grinding-free composite insulator core rod manufacturing method, through specific glue formulations and process steps, including uniform mixing of epoxy resin, curing agent, accelerator, coupling agent and internal mold release agent, and introducing glass fiber into the mold for Pultrusion molding, after forming, clean the bonding surface, apply the organic polysiloxane adhesive, and cover the protective sleeve of silicone rubber or fluorosilicone rubber.

Benefits of technology

The mandrel is achieved without grinding after forming, keeping the shape unchanged, improving the strength of the interface connection between the mandrel and the metal tool and the mass stability of the composite insulator, while avoiding dust pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004832358920000031
    Figure BDA0004832358920000031
  • Figure BDA0004832358920000041
    Figure BDA0004832358920000041
  • Figure BDA0004832358920000051
    Figure BDA0004832358920000051
Patent Text Reader

Abstract

The invention discloses a method for manufacturing a core rod of a composite insulator without grinding. The core rod raw materials include a sizing material and glass fiber. The sizing material includes, by mass ratio, 100 parts of epoxy resin, 75-85 parts of curing agent, 1.5-2 parts of accelerator, 0.5-2 parts of coupling agent and 1-2 parts of internal mold release agent; the internal mold release agent contains a combination of fatty alcohol-C12-15-polyoxyethylene ether, 2,2',2"-trihydroxytriethylamine and tetraphosphoric acid; the coupling agent is BYK-C8001; the sizing material and the glass fiber are formed by a mold. After molding and curing, the bonding surface of the core rod is cleaned without polishing, and then an organic polysiloxane adhesive is applied to the bonding surface, and then dried; finally, a protective sleeve is coated on the bonding surface of the core rod by injection or extrusion molding. The core rod of the present invention does not need to be polished after molding, which saves time and labor, and has no dust pollution; compared with the polished core rod, the core rod can maintain the shape stability after molding after being polished, thereby ensuring the interface connection strength between the core rod and the hardware, and improving the quality stability of the composite insulator; and the core rod can be stored for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite insulators, in particular to a method for manufacturing a core rod of a composite insulator free of grinding. Background Art

[0002] The core rod for composite insulator is generally formed by continuous pultrusion process using glass fiber and resin compound through metal mold. Since the resin has strong bonding strength with metal and the shrinkage rate of the resin after curing is extremely low, there are problems such as difficulty in demoulding and low mold life. Therefore, in order to facilitate demoulding, an internal mold release agent must be added to the core rod raw material. At present, special stearic acid or zinc stearate or a mixture thereof is generally used as an internal mold release agent, but this type of internal mold release agent does not participate in the curing reaction. As time goes by, the internal mold release agent migrates to the core rod surface (bonding surface) and affects the bonding performance of the bonding interface between the core rod and the umbrella sleeve, thereby affecting the stability and service life of the composite insulator.

[0003] In the prior art, in order to ensure the connection performance of the core rod, the formed core rod needs to be polished, but the shape and size accuracy of the core rod after polishing is reduced, which affects the reliability and consistency of the crimping of the insulator hardware. In addition, the dust caused by the polishing of glass fiber and resin is easy to pollute the environment and affect the health of the operators.

[0004] Therefore, there is an urgent need to develop a grinding-free composite insulator core rod manufacturing method that can ensure reliable interface connection strength between the core rod, the umbrella sleeve and the hardware while eliminating the need for grinding the core rod. Summary of the invention

[0005] To solve the above problems, the technical solution adopted by the present invention is as follows:

[0006] A method for manufacturing a core rod of a composite insulator without grinding, characterized in that: the core rod raw material includes a rubber compound and glass fiber, and the rubber compound includes, by mass ratio, 100 parts of epoxy resin, 75-85 parts of curing agent, 1.5-2 parts of accelerator, 0.5-2 parts of coupling agent and 1-2 parts of internal release agent;

[0007] The coupling agent is BYK-C8001;

[0008] The internal mold release agent contains a combination of fatty alcohol-C12-15-polyoxyethylene ether, 2,2′,2″-trihydroxytriethylamine and tetraphosphoric acid.

[0009] The manufacturing process of the grinding-free composite insulator core rod includes the following steps:

[0010] S1, mixing the rubber materials evenly to obtain raw material A;

[0011] S2, introducing glass fiber into the mold and injecting raw material A, using pultrusion process to form and solidify to obtain a core rod;

[0012] S3, clean the bonding surface of the mandrel of S2 without grinding (you can use alcohol or other solvents for cleaning) and dry it;

[0013] S4, applying an organic polysiloxane adhesive on the bonding surface of the mandrel, and then drying it;

[0014] S5. Covering the bonding surface of the mandrel with a protective sleeve (by injection molding or extrusion molding), wherein the material of the protective sleeve is silicone rubber or fluorosilicone rubber;

[0015] S6. Store the mandrel.

[0016] Furthermore, the rubber compound also includes 0.5 to 1 part of a polyether polyol toughening agent.

[0017] Furthermore, the rubber compound also includes ≤10 parts of filler, and the filler is AL(OH)3 or CaCo3.

[0018] Furthermore, the curing agent is one or a combination of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride or methylnadic anhydride.

[0019] Furthermore, the accelerator is 2-ethyl-4-methylimidazole or alkyl-substituted imidazole or K54 tertiary amine accelerator.

[0020] Furthermore, the epoxy resin is one or a combination of 128 epoxy resin or multifunctional composite epoxy resin.

[0021] Furthermore, the drying process is required to be dried at room temperature for more than 20 minutes or dried at a temperature of 100 to 125° C. for 10 to 30 minutes.

[0022] Furthermore, the thickness of the protective cover is less than 2 mm.

[0023] Furthermore, the mass ratio of the internal mold release agent components is 70-75% of fatty alcohol-C12-15-polyoxyethylene ether, 15-20% of 2,2′,2″-trihydroxytriethylamine and 5-10% of tetraphosphoric acid.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. After the core rod is formed, the bonding surface does not need to be polished, saving time and effort and no dust pollution.

[0026] 2. Compared with the polished core rod, the core rod can keep its shape unchanged after being formed after being polished, thereby ensuring the interface connection strength between the core rod and the hardware and improving the quality stability of the composite insulator.

[0027] 3. By using the internal release agent and coupling agent combination of the present invention and coating the protective cover on the bonding surface of the molded core rod, the core rod can be stored for a long time. The injection umbrella cover will not affect the bonding performance of the umbrella cover within 1 year of storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] none DETAILED DESCRIPTION

[0029] For the convenience of understanding the present invention, a more comprehensive description is given below to provide preferred embodiments of the present invention. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0031] The present invention is further described below with specific embodiments:

[0032] In the embodiments of the present invention, the names and amounts of the adhesive components are shown in the following table (adhesive component table).

[0033]

[0034] The internal mold release agent contains fatty alcohol-C12-15-polyoxyethylene ether, which has strong surface activity and can reduce the surface tension of the liquid surface, making the liquid easier to wet and penetrate. The hydrophobic carbon chain group in fatty alcohol-C12-15-polyoxyethylene ether is tightly adsorbed to the epoxy matrix through hydrogen bonds and van der Waals forces; the hydrophilic group can fully stretch in the epoxy resin matrix to form a coating layer on the surface of the matrix. This group can automatically orient on the core rod surface (bonding surface) to demold and stabilize the matrix. Tetraphosphoric acid in the internal mold release agent can improve the stability of the internal mold release agent in high-temperature molding, and at the same time adjust the pH value of the rubber material, so that a certain amount of polar functional groups are added to the resin matrix, making it have good compatibility with the epoxy resin, and at the same time helping to improve the interface performance of the core rod. In addition, 2,2′,2″-trihydroxytriethylamine in the release agent forms a stable colloid with the group containing fatty acid or fatty alcohol, which plays an emulsifying and thickening role and is conducive to demoulding. The polyoxyethylene ether end has good compatibility with silicone rubber through the action of coupling agent and glass fiber, which is convenient for bonding with silicone rubber or fluorosilicone rubber.

[0035] BYK-C8001 is a coupling agent with a long-chain molecular structure produced by BYK Chemicals. One end is a group that is active to internal mold release agents, toughening agents, and epoxy groups, and the other end is a group that is active to inorganic substances such as glass fibers and fillers. The middle section is a group that is compatible with the resin, which can combine the internal mold release agent, toughening agent, and filler with the resin and dissolve them in the resin.

[0036] In this embodiment, the BYK-C8001 coupling agent and the above-mentioned internal mold release agent are used in combination to prevent the internal mold release agent and other components from migrating to the bonding surface of the core rod after the core rod is formed and affecting the interface bonding performance. The disadvantage that the core rod needs to be polished when using the traditional internal mold release agent is overcome, the bonding performance of the core rod is improved, and it has the advantages of saving time and labor and no dust pollution.

[0037] Compared with the polished core rod, the core rod can keep its shape unchanged after being formed after being polished, thereby ensuring the interface connection strength between the core rod and the hardware and improving the quality stability of the composite insulator.

[0038] The curing agent is selected from one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride or methylnadic anhydride.

[0039] The accelerator is 2-ethyl-4-methylimidazole, alkyl substituted imidazole or K54 tertiary amine accelerator.

[0040] The epoxy resin is one or a combination of 128 epoxy resins or multifunctional composite epoxy resins.

[0041] The above-mentioned Examples 1-3 are continuously pultruded into a core rod with a diameter of 24 mm through a mold according to steps S1-S2 of the grinding-free composite insulator core rod manufacturing method, and then tested according to DL / T 1580-2021. The basic performance data of the core rod are shown in the following table (basic performance data of the core rod).

[0042]

[0043] The above-mentioned Examples 1-3 and the comparative example (the internal release agent of the comparative example is stearic acid, and the other components and amounts are the same as those of Example 3) are respectively made into three core rod samples with a diameter of 24 mm, without a protective cover and with a protective cover according to steps S1-S2 and S1-S5 of the grinding-free composite insulator core rod manufacturing method.

[0044] In this embodiment, the thickness of the protective cover is less than 2 mm. After testing, it is found that when the thickness of the protective cover is greater than 2 mm, eccentricity is prone to occur, resulting in the sample (core rod with protective cover) being uneven in the mold cavity during the subsequent injection of the umbrella cover, thereby affecting the bonding performance.

[0045] The core rod with protective cover is tested for water diffusion according to GB / T 22079-2019, and the core rod without protective cover is tested according to DL / T1580-2021. The test results are shown in the table below (core rod water diffusion test data table).

[0046]

[0047] It can be seen from the core rod water diffusion test data table that when using the currently commonly used stearic acid as the internal release agent, after grinding-free and with a protective cover, the internal release agent migrates to the core rod surface and has a great impact on the bonding surface, resulting in a leakage current greater than 100μA in the water diffusion test, which does not meet the requirements of GB / T 19519-2014 standard.

[0048] The above-mentioned Examples 1-3 and the comparative example (the internal mold release agent of the comparative example is stearic acid, and the other components and amounts are the same as those of Example 3) are respectively made into core rods with a diameter of 24 mm, core rods without protective sleeves, and core rods with protective sleeves according to the steps S1-S2 and S1-S5 of the method for manufacturing the core rod of the composite insulator without grinding. After the core rods are stored for a certain period of time (the core rods without protective sleeves are operated in the steps S3 and S4 before the umbrella sleeves are injected), three samples are taken from each of them, and the umbrella sleeves of silicone rubber or fluorosilicone rubber are injected to make FXBW-500 / 120 composite insulators, and the interface bonding performance of the core rods without grinding is tested for 12 consecutive months.

[0049] Test method: The sample to be tested is continuously boiled in a 0.1% NaCl saline solution according to the conditions of GB / T 22079-2019 for 100 hours, and then the interface bonding performance between the umbrella cover and the core rod is tested. The results are shown in the table below (FXBW-500 / 120 umbrella cover interface bonding performance test data table for different storage times of core rods).

[0050] Bonding grade description:

[0051] Level 5: The bonding is very good. After the umbrella cover rubber is torn off, there is only tearing between rubber and rubber, and there is no separation between the rubber (umbrella cover or protective cover) and the core rod. All the samples in a group of samples have no non-sticky parts.

[0052] Level 4: Good adhesion. Only a few individual samples in a group of samples are not adhered locally, and the non-adhesive area accounts for less than 5% of the total adhesion area of ​​the entire group of samples.

[0053] Grade 3: The bonding is relatively poor. After the rubber (umbrella cover or protective cover) is torn off from the core rod, there are many non-stick areas in a group of test pieces, and the non-stick area accounts for 25% of the total bonding area of ​​the entire group of test pieces.

[0054] Level 2: The bonding is very poor. The rubber (umbrella cover or protective cover) is easily torn off from the core rod, leaving a small amount of adhesive. The non-adhesive area accounts for more than 50% of the total bonding area of ​​the entire group of test pieces.

[0055] Level 1---Almost completely non-stick.

[0056]

[0057] From the FXBW-500 / 120 umbrella cover interface bonding performance test data table made after the core rod is stored for different time periods, it can be seen that:

[0058] 1) In the case of no grinding, the stearic acid internal mold release agent of the comparative mandrel migrates to the mandrel surface (bonding surface) whether it is coated with a protective cover or directly injected with an umbrella cover, which has a great impact on the bonding surface, resulting in poor interface bonding, and the rubber of the umbrella cover or protective cover is easily torn off from the mandrel bonding surface. However, the mandrels of Examples 1-3 of the present invention can obtain good bonding performance when placed for 4 weeks, whether the umbrella cover is injected with or without a protective cover.

[0059] 2) The interface bonding grade of the core rods of Examples 1-3 without protective cover and polishing can be maintained at Grade 5 after the umbrella cover is injected within 4 weeks, and it starts to decline from the 5th week. Therefore, adding the protective cover within one month after the core rod is made can ensure the interface bonding performance of the core rod.

[0060] 3) The core rods of Examples 1-3 can ensure the interface bonding performance within one year of storage when they are protected by a protective cover and do not require grinding.

[0061] The above-mentioned Examples 1-3 and the comparative example (the internal release agent of the comparative example is stearic acid, and the other components and amounts are the same as those of Example 3) are processed into three core rod samples with a diameter of 24 mm and a protective sleeve according to steps S1-S5 of the grinding-free composite insulator core rod manufacturing method, and silicone rubber or fluorosilicone rubber umbrella sleeves are injected on all samples to make FXBW-500 / 120 composite insulators. All test samples were boiled in 0.1% NaCl saline solution for 42 hours according to GB / T 22079-2019, and then the samples with umbrella covers were subjected to steep wavefront impulse withstand voltage test. Finally, they were tested and judged in four sections according to GB / T 19519-2014 and Q / GDW13253.1-2019 "10kV~1000kV AC Rod-shaped Suspension Composite Insulator Procurement Standard Part 1: General Technical Specifications". The results are shown in the table below (FXBW-500 / 120 composite insulator dry power frequency voltage test data and results).

[0062]

[0063] The method for manufacturing a grinding-free composite insulator core rod comprises the following steps:

[0064] S1, mixing the rubber materials evenly to obtain raw material A;

[0065] S2, introducing glass fiber into the mold and injecting raw material A, and obtaining a core rod after solidification and molding;

[0066] S3, clean the bonding surface of the mandrel of S2 with alcohol without polishing and dry it;

[0067] S4, applying an organic polysiloxane adhesive on the bonding surface of the mandrel, and then drying it;

[0068] S5. Covering the bonding surface of the mandrel with a protective sleeve by injection molding or extrusion molding, wherein the material of the protective sleeve is silicone rubber or fluorosilicone rubber;

[0069] S6. Store the mandrel.

[0070] The manufacturing method of FXBW-500 / 120 composite insulator is as follows:

[0071] SS1. Put the prepared umbrella cover rubber into the injection machine and adjust the injection parameters;

[0072] SS2, take the mandrel stored in the above step S6, clean the bonding surface of the protective cover and put it into the mold cavity;

[0073] SS3, mold closing, injection chute, vulcanization molding;

[0074] SS4, take out and enter the post-process.

[0075] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.

Claims

1. A method for manufacturing a grinding-free composite insulator core rod, characterized in that: The core rod raw material includes rubber and glass fiber, and the rubber includes, by mass ratio, 100 parts of epoxy resin, 75-85 parts of curing agent, 1.5-2 parts of accelerator, 0.5-2 parts of coupling agent and 1-2 parts of internal release agent; The coupling agent is BYK-C8001; The internal mold release agent contains, by mass percentage, 70-75% of fatty alcohol-C12-15-polyoxyethylene ether, 15-20% of 2,2′,2′′-trihydroxytriethylamine and 5-10% of tetraphosphoric acid; The manufacturing process of the grinding-free composite insulator core rod includes the following steps: S1, mixing the rubber materials uniformly to obtain raw material A; S2, introducing the glass fiber into a mold and injecting the raw material A into the mold, using a pultrusion process to form and solidify the core rod; S3, clean and dry the mandrel bonding surface of S2 without grinding; S4, applying an organic polysiloxane adhesive on the bonding surface of the mandrel, and then drying it; S5. Covering the bonding surface of the mandrel with a protective sleeve, wherein the material of the protective sleeve is silicone rubber or fluorosilicone rubber; S6. Store the mandrel.

2. The method for manufacturing a grinding-free composite insulator core rod according to claim 1, characterized in that: The rubber compound also includes 0.5 to 1 part of a polyether polyol toughening agent.

3. The method for manufacturing a grinding-free composite insulator core rod according to claim 1, characterized in that: The rubber compound further comprises ≤10 parts of filler, and the filler is AL(OH)3 or CaCo3.

4. The method for manufacturing a grinding-free composite insulator core rod according to claim 1, characterized in that: The curing agent is one or a combination of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride or methylnadic anhydride.

5. The method for manufacturing a grinding-free composite insulator core rod according to claim 1, characterized in that: The accelerator is 2-ethyl-4-methylimidazole or alkyl substituted imidazole or K54 tertiary amine accelerator.

6. The method for manufacturing a grinding-free composite insulator core rod according to claim 1, characterized in that: The epoxy resin is one or a combination of 128 epoxy resin or multifunctional composite epoxy resin.

7. The method for manufacturing a grinding-free composite insulator core rod according to claim 1, characterized in that: The drying process is required to be dried at room temperature for more than 20 minutes or dried at a temperature of 100-125° C. for 10-30 minutes.

8. The method for manufacturing a grinding-free composite insulator core rod according to claim 1, characterized in that: The thickness of the protective cover is less than 2 mm.

Citation Information

Patent Citations

  • Core rod for composite insulator and manufacturing method thereof

    CN114783699A

  • Anti-mildew and anti-algae silicone rubber material for composite insulator umbrella cover

    CN117887264A